The logistics sector in Kazakstan: a swot analysis - Assanova, A. D.; Akhmetova, Z. B.; Bianchi, Isaías Scalabrin (Farabi Journal of Social Sciences, 2021)
Logistics plays a significant role in the change and enhancement of economic measures as well as to the growth of business around the world. The framework is important for incorporation of Kazakhstan’s economy into the global transport economy. The favorable geographical location of Kazakhstan between Europe and Asia defines its major transit transport capacity and provides an excellent opportunity to serve as a transcontinental Eurasian bridge, providing Asian countries with a single land transport link to Europe and Russia. Kazakhstan needs to make every effort to develop an effective and technologically upgraded transport system to promote the accelerated delivery to the foreign market of domestic exports of goods. The globalization of international economic correlative enforce new stipulation on the effectiveness of transport and logistics substructure and determines the need to improve transport technologies and provide appropriate logistics services. This article aimed at testing the logistics sector in the Republic of Kazakhstan. With the purpose of accomplish this goal, this study carried out a qualitative analysis based on the lens from theory with reports, articles and information about the logistics sector. Research findings were derived from swot analysis that shows the main problems and perspectives of the logistics sector. The article ends with suggestions and recommendations to the logistic sector. Key words: logistics, transport, literature review, economy, Swot analysis.